Hubungan Komunikasi Perawat dengan Tingkat Kepuasan Pasien Rawat Inap di RSUD Undata Provinsi Sulawesi Tengah - Sinta Astuti Pasau; Elifa Ihda Rahmayanti; Widyawati L Situmorang (Universitas Widya Nusantara, 2025)
Effective communication is a crucial component of nursing services and plays a significant role in determining patient satisfaction, particularly in inpatient care where nurses interact directly and continuously with patients. This study aimed to analyze the relationship between nurse communication and the level of inpatient satisfaction at Undata Regional General Hospital, Central Sulawesi Province. This study employed a quantitative approach with an analytical survey design using a cross-sectional method. A total of 75 inpatients were selected as respondents using a cluster sampling technique. Data were collected using validated and reliable questionnaires on nurse communication and patient satisfaction. Data analysis was performed using the chi-square test with the assistance of SPSS software. The results showed that the majority of respondents perceived nurse communication as effective (68.0%) and reported satisfaction with inpatient services (65.3%). Statistical analysis indicated a significant relationship between nurse communication and inpatient satisfaction (p < 0.05). Therefore, hospital management should pay special attention to improving the quality of nursing communication through regular patient satisfaction evaluations, performance feedback for nurses, and the development of standard operating procedures (SOPs) that emphasize humane and effective communication.